Seasonal and storm flow dynamics of dissolved organic carbon in a Mediterranean mountain catchment (Vallcebre, eastern Pyrenees). Issue 1 (2nd January 2017) - Roig-Planasdemunt, Maria; Llorens, Pilar; Latron, Jérôme
ABSTRACT: To improve understanding of DOC dynamics in seasonal Mediterranean environments, rainfall, soil water, groundwater and stream water samples were taken during a 27-month period in the Can Vila catchment (northeast Spain). Using these data, we characterized DOC dynamics in the different hydrological compartments and analysed the factors affecting them. We also analysed DOC dynamics during storm events and the factors that control DOC delivery to the stream. The results show some seasonality in rainwater and soil water DOC concentrations, while no clear seasonality was observed in stream water and groundwater, where DOC dynamics were strongly related to discharge and water table variations. For storm events with several discharge peaks, the slope of the discharge–DOC concentration relationship was higher for the first peak. The rather similar dynamics of stream water DOC concentration in all floods contrast with the observed diversity of hydrological processes. This raises the question of the origin of the observed rapid DOC increase.EDITOR M.C. Acreman ASSOCIATE EDITOR K. Heal